1997
DOI: 10.1046/j.1365-2249.1997.4351455.x
|View full text |Cite
|
Sign up to set email alerts
|

N-3 polyunsaturated fatty acids modulate the expression of functionally associated molecules on human monocytes and inhibit antigen presentation in vitro

Abstract: SUMMARYN-3 polyunsaturated fatty acid (PUFA)-rich diets are associated with suppression of cell-mediated immune responses, but the mechanisms are unclear. Specific immune responses are initiated by antigenpresenting cells (APC). We have previously shown in vitro that the n-3 PUFA, eicosapentaenoic acid (EPA), inhibits the expression of HLA-DR, an MHC class II molecule required for normal APC function on human blood monocytes. In contrast, docosahexaenoic acid (DHA) enhanced the expression of this molecule on u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
1
4

Year Published

1998
1998
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 21 publications
0
32
1
4
Order By: Relevance
“…Still other studies have shown that linoleic acid (n-6) decreases the activity of IL-2 [129], and increases IL-1 production and tissue response to cytokines, while n-3 generally decreases IL-1 production and activity [44]. Despite some disagreement among studies, it seems that n-3 fatty acids (alpha-linolenic acid, DHA, EPA) decrease the production and activity of the pro-inflammatory cytokines (IL-1, IL-6, TNF alpha ) [13,20,52,124] and that n-6 family has the opposite effect [19,44,54]. The ability of n-3 PUFA to reduce pro-inflammatory cytokines and prostaglandin [21] lead to the proposal for the use of fish oil to relieve pain.…”
Section: Pufa and The Immune Systemmentioning
confidence: 99%
“…Still other studies have shown that linoleic acid (n-6) decreases the activity of IL-2 [129], and increases IL-1 production and tissue response to cytokines, while n-3 generally decreases IL-1 production and activity [44]. Despite some disagreement among studies, it seems that n-3 fatty acids (alpha-linolenic acid, DHA, EPA) decrease the production and activity of the pro-inflammatory cytokines (IL-1, IL-6, TNF alpha ) [13,20,52,124] and that n-6 family has the opposite effect [19,44,54]. The ability of n-3 PUFA to reduce pro-inflammatory cytokines and prostaglandin [21] lead to the proposal for the use of fish oil to relieve pain.…”
Section: Pufa and The Immune Systemmentioning
confidence: 99%
“…It has been found that monocytes treated with eicosapentaenoic acid (EPA) have lower expression of ICAM-1, an effect that is opposite to that of docosahexaenoic acid (DHA) (5). After monocyte stimulation, it has been found that both EPA and DHA (omega-3 fatty acids) had a reduced expression of ICAM-1 (5).…”
Section: Chemotaxis Adhesion and Diapedesismentioning
confidence: 99%
“…Monocytes from animals fed diets rich in omega-3 fatty acids (fish oil) have lower antigen-presenting capability (5), that may be associated with a decreased expression of major histocompatibility complex II (MHC II) molecules on macrophages, which are essential for antigen presentation to lymphocytes (5). PUFAs, especially DHA, can inhibit the expression of these molecules in INF-gamma-stimulated cells.…”
Section: Production Of Cytokines and Other Cell Mediators Antigen Prmentioning
confidence: 99%
See 1 more Smart Citation
“…While the majority of these studies have taken place in mice, similar effects have been found also in human subjects. For example, dietary FO suppressed the ability of macrophages to present antigen to T lymphocytes (Hughes et al 1997). T lymphocyte IL-2 secretion and subsequent proliferation was significantly suppressed by FO supplementation in human subjects (Endres et al 1993).…”
Section: Effect Of N-3 Fatty Acids On the Immune Systemmentioning
confidence: 99%